Fun with Clothes Project Book - Shona Armstrong; Johannah Pourciau; Joy Cantrell Jordan; R. Nadine Hackler (EDIS)
This document is 4HCCM10 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published in 1994; Reviewed June 2002.